Aqueous film-coating with the ultra-coater (hybrid coater) - Kwok, Swee Har Teresa (Curtin University, 2004)
Hydroxypropylmethylcellulose (HPMC), which is available in different degrees of substitution and viscosity designations, is one of the most commonly used cellulosic polymers in aqueous film coating. It is relatively easy to process due to its non-tacky nature and has been known to produce smooth and clear films. For aqueous film coating, it is cost effective to use a coating formulation containing a high concentration of polymer without affecting the viscosity or spray rate and compromising on the quality of the film coat. Hence, it is ideal to use a polymer of low viscosity grade. The rheological properties of HPMC with various viscosity grades were determined. It was found that HPMC Methocel E3 had the lowest viscosity and was the least affected by the increase in polymer concentration. Additives can modify the film properties, including the glass transition temperature of the coating polymer. Glass transition temperature influences the viscosity of the coating solution and the mechanical properties, adhesion and permeability of the film coat. Various concentrations of different additives were incorporated in HPMC formulations to study the effect on these properties. Some long-chain fatty acids were included in the study to investigate if their hydrophobic carbon chains could retard moisture permeation of HPMC films. It was observed that HPMC films containing water-soluble additives produce films with clarity similar to those without additives, whereas those with hydrophobic additives tend to be patchy or hazy in appearance. A vinyl pyrrolidone / vinyl acetate copolymer (S630) was investigated for its influence on HPMC films, comparing the results with a commonly used plasticizer, polyethylene glycol (PEG) and another copolymer, polyvinyl alcohol (PVA). Intrinsic properties of the solutions, such as viscosity and glass transition temperature, were evaluated.The effect of S630 on the film properties, such as physical appearance, surface roughness, moisture permeation and mechanical properties, as well as its ability to promote better adhesion of the film coat to the core surface, were compared. S630 was found to be effective both as a film-former and plasticizer, reducing the glass transition temperature and viscosity, but enhancing the tensile strength, elongation and work of failure of the cast film. The water vapour permeability was slightly increased but not to the same extent as with polyethylene glycol PEG). A 10% concentration of this copolymer increased the adhesive strength and toughness of the HPMC film coat. Aqueous film coating was carried out in the ultra-coater, using HPMC coating formulations containing 8% w/w of solids, without or with 10% concentration (based on dry weight of total solids) of the additives, PEG, polyvinyl alcohol (PVA) and S630, for coating the tablets. Capsule-shaped lactose tablet cores of specific surface area, hardness, weight, friability and disintegration time were used to study the process variables. Process variables, including air flow rate, temperature and humidity, coating application rate or pump flow rate, atomising air pressure and speed of the rotating disk, were investigated in order to obtain the optimum operating conditions for these solutions. It was found that the process parameters were similar for all the coating formulations containing 8% solid. The additives used in the coating formulations had little influence on the coating process. The ultra-coater was an effective unit for the aqueous film coating of tablets with a batch size of not less than 5 kg.